Developing a Framework for the 3D Visualization of underground Petroleum Pipelines - Balogun, Abdul-Lateef (World Academy of Research and Publication, 2011)
A common source of damage to subsurface petroleum pipelines is their accidental cutting by excavation workers, oblivious of the precise underground location of the pipelines. Such blind cuttings have had catastrophic consequences in the past. Lives and properties are often lost in the wake of explosions that accompany blind cuttings of underground petroleum pipelines. Because of their capability to render accurate, three dimensional views of these pipelines thereby drastically reducing the possibility of accidental cuts, three dimensional (3D) maps are increasingly becoming popular. However, one major drawback is the exorbitant cost of most of the Geographical Information System (GIS) packages that support the 3D modeling and visualization of subsurface pipelines. Furthermore, the advanced languages used in building many of these packages make it difficult for non-GIS experts, field workers,and other professionals to relate with them. Since people from diverse disciplines (without strong GIS background) need to visualize and analyze these subsurface pipelines on a regular basis, it is pertinent to develop a system capable of performing basic 3D visualization functions, in addition to being user-friendly and highly affordable. This paper, which proposes a framework to achieve this purpose, is part of an ongoing research on the subject matter.